Analisis Kepuasan Pengguna Terhadap Penerapan Sistem Informasi Terpadu Layanan Prodi (SIPLO) Menggunakan End User Computing Satisfaction (EUCS) - Vina Zahrotun Kamila (Department of Information Technology, Universitas Timor, Indonesia, 2023)
SIPLO is information system created and developed in order to manage academic activity scheduling data so that it can make it easier for users in intranet and internet campus academic activities. This study aims to determine the level of satisfaction of the Sistem Informasi Terpadu Program Studi (SIPLO) using the End User Computing Satisfaction (EUCS) model which includes 5 variables, namely content, accuracy, format, easy of use and timeliness. The results of the study showed that the satisfaction level of SIPLO users was 24% very satisfied, 52% satisfied, 21% quite satisfied, 2% dissatisfied and 1% very dissatisfied. The results of the hypothesis test showed that 5 variables had an effect on satisfaction and the hypothesis was accepted while the other 2 variables had no effect on satisfaction and the hypothesis was rejected.